2020
DOI: 10.1097/brs.0000000000003400
|View full text |Cite
|
Sign up to set email alerts
|

Systematic Review of Outcomes Following 10-Year Mark of Spine Patient Outcomes Research Trial for Intervertebral Disc Herniation

Abstract: Mini We summarized the 10-year outcomes of Spine Patient Outcomes Research Trial for intervertebral disc herniation through a systematic review. The observational cohort 2-year analysis and the as-treated analysis of the randomized control trial at 4 and 8 years showed statistically greater improvements in those patients who were treated surgically. Study Design. We performed a comprehensive search of Pubmed, MEDLINE, and EMBASE for English-language stu… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
7
0
1

Year Published

2021
2021
2024
2024

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 10 publications
(8 citation statements)
references
References 36 publications
0
7
0
1
Order By: Relevance
“…The lack of symptoms may be a consequence of the nature of the tear, location, and severity of the injury. Symptomatic lumbar disc herniations that do not resolve with initial appropriate nonoperative management are often managed surgically 71 . While surgical intervention decompresses neural elements and removes the herniated component of the disc, there is no successful method to clinically repair the AF.…”
Section: Annulus Fibrosus Injurymentioning
confidence: 99%
“…The lack of symptoms may be a consequence of the nature of the tear, location, and severity of the injury. Symptomatic lumbar disc herniations that do not resolve with initial appropriate nonoperative management are often managed surgically 71 . While surgical intervention decompresses neural elements and removes the herniated component of the disc, there is no successful method to clinically repair the AF.…”
Section: Annulus Fibrosus Injurymentioning
confidence: 99%
“…Having intractable pain and failing ambulatory conservative treatment essentially means that all of this patient subset consists of potential surgical candidates, meeting similar inclusion criteriae to the patients randomized in previous studies comparing conservative to surgical treatment 2 , 4 , 5 , 10 , 18 .…”
Section: Introductionmentioning
confidence: 99%
“…The mechanism of radicular pain in disc herniation may relate to mechanical compression or inflammation [ 1 , 7 - 10 ]. While surgical interventions are considered the mainstay of treatment for lumbar disc herniation or radiculopathy [ 11 ], multiple studies have shown epidural injections to be effective [ 1 , 10 ].…”
Section: Introductionmentioning
confidence: 99%